Literary searches of Kazakh dramaturgy in totalitarian system - Takirov, S.U.; Zhakulaev, A.M. (KU Publ., 2021)
This article is devoted to the literary traces of Kazakh drama in the 30s and 40s of the XX century, the consequences of ideological pressure in post-revolutionary literature and the transition of the nation's spirituality from collapse to collapse. The resolutions in literature and art, adopted in the 1930s, guided by the creation of socialism in Kazakhstan, marked the playwrights as “nationalist”, “alashist”, “enemy of the people”, repressed poets and writers, and aimed to ensure that the literary process did not deviate from the path of Marxist-Leninist teaching. Although the the plays of originators of Kazakh drama such as M. Auezov, Sh. Kussainov, A. Abishev were actively discussed in literary criticism, achievements and gaps in the development of drama were studied. The articles of researchers in poetry, prose, and drama of M. Auezov, S. Mukanov, M. Gabdullin, A. Tokmagambetov, G. Musrepov, E. Ismailov, etc. have been re-differentiated and interpreted from the point of view of the present day in determining the direction of artistic development of the literary process of that period. This article considers the directions of development of Kazakh drama in the totalitarian system under the Soviet government from this point of view.
Тоталитарлық жүйедегі қазақ драматургиясындағы ізденістер
Литературные изыскания в казахской драматургии при тоталитарном режиме
Keywords: literary criticism; drama; Kazakh drama; totalitarian system; literary development; Marxist- Leninist doctrine; literary process; nationalism; critical attitude; party